Chronic lead intoxication and growth and cognitive-emotional development in children - Vega, Julián (2003)
Objetive: To determine the association between chronic lead intoxication and growth and cognitiveemotional development alterations in children at “María Reiche” school - Callao. Design: Crossectional study. Material and methods: To 70 children 8 to 12 year-old from “María Reiche” school (A.A.H.H. “Puerto Nuevo”- Callao), who had participated in a survey blood lead screening (General Direction of Environmental Health, in 1999), we applied instructions monitoring tests, communicative, motor, manipulator, and academic abilities test as well as anxiety checkup list. The intellectual coefficient and BMI (body mass index) were measured. Chi square, t-Student and simple lineal correlation tests were employed for prosecution of data using the statistical package SPSS version 11.0 with a 95% confidence level. RESULTS: By chi square test there was a significant (p=0,025) relation between blood lead levels and degrees of anxiety. There was significant difference between anxiety check-up list score averages and categorization of lead levels by t-Student test (p=0,031). The relation between blood lead levels and intellectual coefficient, as well as communicative, motor, academic, manipulator abilities, monitoring of instructions and body mass index did not turn out to be significant. Conclusion: There is an association between chronic lead intoxication and anxiety degree (emotional development). However, there was no association with growth or cognitive development.